Rencana Bisnis Pengembangan Usaha Aplikasi "ASCENT (Asian Cinema Net)" Aplikasi Penyedia Video Nonton Online - Chairunnisa, Angellifa Trinida; Ernanda, Mercedes Daimler Benz; Shiwan, Dona Sarus; Ardani, Sabrina Puspa; Rahayu, Winda Tri; Septiyana, Silva; Suwandi, Suwandi (Journal of Entrepreneurship, Management and Industry (JEMI), 2020)
Writing this article is an ASCENT application engaged in online watching services, with a service that makes it easy for customers to enjoy various movies online. The ASCENT application was built by providing entertainment services in the form of films from Asian countries. This article discusses implementing, analyzing, and also discussing business together with financial predictions, and companies’ strength. This business analysis method uses SWOT analysis and marketing mix.